Unveiling the Multifaceted Driving Mechanism of Digital Transformation in the Construction Industry: A System Adaptation Perspective - Mengqi Yuan; Wenfei Zang; Long Li; Ziwei Yi (Systems)
Various industries see digital transformation (DT) as the pillar to coping with intensified competition, energy crises, and climate change. As a critical sector for DT, the construction industry’s project-oriented paradigm and immature industrialized production method limit the research on emerging digital technology and ignore the theoretical mechanism. Through the lens of system adaptability, this study proposes a multifaceted model to examine the DT effectiveness and unveil the driving mechanism. (1) An extensive literature review, action research, and the nominal group technique identified 21 determinants, which were categorized into a technological–organizational–environmental (TOE) framework to analyze the construction industry’s DT determinants from multiple dimensions. (2) This research utilizes data from 272 respondents collected through field research, with a survey designed to measure the relationships among variables. (3) Structural equation modeling (SEM) through Analysis of Moment Structures (AMOSs) has been used to analyze the hypotheses and analyze the impact of determinants from various dimensions on DT and examine their influence pathways. The results indicate that determinants in the technological, organizational, and environmental dimensions positively affect DT’s success in the construction industry. The influence of the technological dimension is the strongest, and the organizational dimension is the weakest. The research findings offer valuable recommendations and insights for stakeholders in the construction industry, highlighting the importance of considering these three dimensions to enhance the overall effectiveness of DT when driving industry transformation and upgrading. Additionally, this study uses the TOE framework to reveal determinants from multiple dimensions. It combines SEM to explore the pathways of their effects, offering key theoretical insights for the body of knowledge.